Monetary Policy and Racial Inequality - Alina K. Bartscher; Moritz Kuhn; Moritz Schularick; Paul Wachtel (Center for Economic Studies and Ifo Institute (CESifo), 2021)
This paper aims at an improved understanding of the relationship between monetary policy and racial inequality. We investigate the distributional effects of monetary policy in a unified framework, linking monetary policy shocks both to earnings and wealth differentials between black and white households. Specifically, we show that, although a more accommodative monetary policy increases employment of black households more than white households, the overall effects are small. At the same time, an accommodative monetary policy shock exacerbates the wealth difference between black and white households, because black households own less financial assets that appreciate in value. Over multi-year time horizons, the employment effects are substantially smaller than the countervailing portfolio effects. We conclude that there is little reason to think that accommodative monetary policy plays a significant role in reducing racial inequities in the way often discussed. On the contrary, it may well accentuate inequalities for extended periods.
Keywords: E40; E52; J15; 330; monetary policy; racial inequality; income distribution; wealth distribution; wealth effects